Technoeconomic Assessment of Gasifier Baking Stoves for Commercial Purposes - Assefa Tesfaye Hailu; Tayachew Nega; Leliso Hobicho (Journal of Engineering)
The energy supply in Ethiopia is dominated by biomass energy, mainly for household consumption. The development of gasification-based gasifier baking stoves for energy demand is the subject of this study. The novelty of the gasifier baking stove is its ability to bake food more quickly while using less wood fuel. Biomass fuels are used inefficiently in poorly ventilated kitchens, resulting in indoor air pollution and the consumption of large amounts of wood fuel. Biomass gasifier baking stoves can improve fuel efficiency, baking time, and indoor air pollution while producing char as a byproduct. The proposed new gasifier study shows an average fuel use efficiency of 45% and time savings of 12% compared to Mirt stoves. Furthermore, the grate cover of the biomass gasifier stove is also used to regulate the airflow rate. The primary air that enters the reactor is controlled by a manually operated slide grate cover. The water boiling test and control cooking test were developed to mirror the performance of a modern baking and cooking stove. The baking stove was tested with Eucalyptus globulus as a feedstock. A technoeconomic assessment was conducted on a biomass gasifier baking stove for commercial purposes. For the technoeconomic assessment, we mostly employed the simple payback period projection. The economic analysis was conducted using Ethiopian supply and market rates, which may differ from region to region. The baking stove has an initial capital cost of about 15,100 ETB and a payback period of 2.49 years, which makes it economically viable for those living in remote locations. According to the study, the typical emissions from a biomass gasifier stove running on eucalyptus wood fuel are 0.24 ppm CO and 8.91 ppm CO2. The results of the stove’s economic study demonstrate that using eucalyptus wood fuel results in a shorter payback period. The performance efficiency of the new gasifier stove in terms of wood fuel and time saving as compared to the Mirt stove is 45% and 12%, respectively.